REPRESENTATION OF INDONESIAN CULTURE IN “ONLY IN INDONESIA” VIDEO BY LASTDAY PRODUCTION - Andre Ikhsano; Yolanda Stellarosa; Lusiana Cindy Irawan; Mengmeng Guo (ASPIKOM Jabodetabek Region, 2021)
Culture can be formed from habits acquired by humans as members of society. Indonesia has so many ethnic groups and produces different habits. From the habits carried out by the community; it is not uncommon to have bad habits and unique habits. This is what makes one of the videos with a cultural theme that is considered satire through one of the social media platforms, which is Youtube, entitled